A novel fabrication method for glass foams with small pore size and controllable pore structure. Issue 12 (10th August 2017) - Huo, Wenlong; Yan, Shu; Wu, Jia‐Min; Liu, Jingjing; Chen, Yugu; Qu, Yanan; Tang, Xinyue; Yang, Jinlong
Abstract: In this paper, a novel fabrication method for glass foams has been introduced based on colloidal suspension foaming method using waste glass as starting materials. It is demonstrated for the first time that foam stabilization via in‐situ hydrophobization of waste glass particles is possible. The fabrication conditions for stable glass particle‐stabilized foams are optimized by investigating the influences of pH value, concentration of propyl gallate and ball milling time, respectively. It is demonstrated that this is a versatile method for fabrication of stable foamed glass suspension and final glass foams with small pore size of dozens of microns, which is much smaller than that of most glass foams in previous literatures. This novel method enables both closed pore structure and open pore structure simply by tailoring solid loading of glass suspension. A "sieve‐like" hierarchical pore structure can be achieved by adjusting sintering temperature. The glass foams with controllable structure could be applied in thermal insulation fields for closed pores, and in catalyst loading, filtration, and separation fields for open pores and hierarchical pore structure.